The Effect of Celebrity Endorsement and Perceived Quality on Purchase Intention with Perceived Value as Mediation in Scarlett Cosmetics in Malang City - Aslinda, Aslinda; Sudarmiatin; Wening Rahayu (Profesional Muda Cendekia Publishing, 2024)
Research Aims: This research aims to determine the quality, perceived value, purchase intention influence of Celebrity Endorsement and Perceived Quality on Purchase Intention with Perceived Value as an Intervening Variable among Scarlett cosmetics consumers in Malang City. This research is important to carry out because there is a research gap in previous studies. Design/methodology/approach: This research uses a nonprobability sampling technique with a purposive sampling method. The data collection technique uses a questionnaire distributed to respondents with 5-point Likert scale answers. The sample in this study amounted to 261 respondents with data analysis using the SEM-PLS method SmartPLS4 software Research Findings: The empirical test results show research findings, namely that there is a positive and significant influence between celebrity endorsement on perceived value, there is a positive and significant influence between perceived quality on perceived value, there is a positive and significant influence between celebrity endorsement on purchase intention, there is a positive and insignificant influence between perceived quality on purchase intention, there is a positive and significant influence between perceived value on purchase intention, there is a positive and significant influence of celebrity endorsement on purchase intention through perceived value, and there is a positive and significant influence between perceived quality on purchase intention through perceived value Theoretical Contribution/Originality: This research shows that using celebrity endorsement on Scarlett's cosmetic products can improve purchase intention consumer. Therefore, marketers of skincare products Scarlett's comments on Scarlett's Instagram social media in Malang City can take advantage of these results by designing marketing campaigns that utilize the power of influence celebrity endorsement